Corrections in ink : a memoir - Blakinger, Keri (St. Martin's Press, 2022)
"Corrections in Ink is an electric and unforgettable memoir about a young woman's journey-from the ice rink, to addiction and a prison sentence, to the newsroom-emerging with a fierce determination to expose the broken system she experienced. An elite, competitive figure skater growing up, Keri Blakinger poured herself into the sport, even competing at nationals. But when her skating partnership ended abruptly, her world shattered. With all the intensity she saved for the ice, she dove into self-destruction. From her first taste of heroin, the next nine years would be a blur-living on the streets, digging for a vein, selling drugs and sex, eventually plunging off a bridge when it all became too much, all while trying to hold herself together enough to finish her degree at Cornell. Then, on a cold day during Keri's senior year, the police stopped her. Caught with a Tupperware container full of heroin, she was arrested and ushered into a holding cell, a county jail, and finally into state prison. There, in the cruel "upside down," Keri witnessed callous conditions and encountered women from all walks of life-women who would change Keri forever. Two years later, Keri walked out of prison sober and determined to make the most of the second chance she was given-an opportunity impacted by her privilege as a white woman. She scored a local reporting job and eventually moved to Texas, where she started covering nothing other than: prisons. Now, over her career as an award-winning journalist, she has dedicated herself to exposing the broken system as only an insider could. Not just a story about getting out and getting off drugs, this rich memoir is about finding redemption within yourself, as well as from the outside world, and the power of second chances. Written in a searing voice, Corrections in Ink is told with unflinching honesty and jolts of irreverent humor, and uncovers a dark and brutal system that affects us all"--